Use of plasmid R68.45 for constructing a circular linkage map of the Rhizobium trifolii chromosome. - Megias, M (1982)
Plasmid R68.45 was used to promote conjugal transfer of chromosomal markers in Rhizobium trifolii RS55. Analysis of two-factor and three-factor crosses among R. trifolii strains enabled construction of a circular linkage map of the R. trifolii chromosome, containing 17 nutritional and resistance markers.